Exposure to Short Wavelength-Enriched White Light and Exercise Improves Alertness and Performance in Operational NASA Flight Controllers Working Overnight Shifts. Issue 2 (February 2021) - Barger, Laura K.; Sullivan, Jason P.; Lockley, Steven W.; Czeisler, Charles A.
Abstract : Objective: We evaluated the efficacy of a combined short-wavelength-enriched white light and exercise fatigue countermeasure during breaks for flight controllers working overnight shifts. Methods: Twenty NASA flight controllers were studied for two blocks of nightshifts in ISS mission control, randomized to either the control or countermeasure condition. The countermeasure constituted passive exposure to blue-enriched polychromatic lighting for three 20-minute intervals, which included 10 minutes of exercise and occurred before and twice during their shifts. Alertness, performance, and mood were evaluated. Results: Flight controllers reported being significantly more alert ( P < 0.0001) and happy ( P = 0.003) and had faster reaction times (10% slowest responses; P < 0.05) during the countermeasure condition compared to control. Conclusions: The combined light and exercise countermeasure improved alertness, performance, and mood in shift workers overnight. Further research is necessary to determine their relative contribution.